Regulation of mycorrhiza development in durum wheat by P fertilization: Effect on plant nitrogen metabolism. Issue 3 (14th April 2018) - Di Martino, Catello; Palumbo, Giuseppe; Vitullo, Domenico; Di Santo, Patrick; Fuggi, Amodio
Abstract: The aim of this work was to study the effect of arbuscular mycorrhizal fungus Glomus mosseae on growth and nitrogen (N) metabolism of durum wheat ( Tritcum durum) under various P soil contents. The analyses were extended to macro and micronutrient tissue concentrations, nitrate reductase and glutamine synthetase activities, as well as protein, aminoacids, pyridine dinucleotides and adenine nucleotides. Arbuscular mycorrhiza increased wheat growth in soil in which P availability was low and nitrate was the dominant N form. The root colonization occurred at the highest level in plants grown in limiting soil P and was inversely related to soil P content. The micorrhizal wheat plants contained also the highest concentrations of macro (P, K, Ca, N) and micronutrients (Fe, Zn, Mn) as well as free amino acids, protein, NAD, NADP, AMP, ADP, ATP in roots and leaves. In particular, the micronutrient tissue concentrations (Zn, Mn) supported that mycorrhiza actively modulated their uptake limiting interferences and optimizing growth better than the plant roots, like a very efficient "rootstock". Control plants grown at the highest soil P did not reach the same concentration as the mycorrhizal plants. Nitrate reductase activities in the roots of mycorrhizal plants were higher than in the control ones, while glutamine synthetase activities were highest in the leaves. Protein and amino acids concentrations, as well as AMP, ADP, ATP, NAD(P), and NAD(P)H were also higher than in the control. Among the free amino acids in the roots, the high levels of glutamine, asparagine, arginine, support the view that ammonium was transferred through the arbuscules to the root cells where it was re‐assimilated in the cortical cells, forming high N : C ratio‐amino acids. They were transferred to the leaves where all the other N compounds could be largely synthesized using the carbon skeletons supplied by photosynthesis.